Experimental and numerical analysis of fatigue crack repair in Rib-to-Rib welded connections of orthotropic steel decks using CFRP and steel plates - Shakir, Saifaldien; Mollamahmutoglu, Cagri; Alemdar, Fatih (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Rib-to-rib butt-welded (RRBW) connections are among the most fatigue-critical details in orthotropic steel decks (OSDs), and extensive cracking has been reported in existing bridges. This study investigates the fatigue repair of cracked RRBW connections using two lightweight retrofit strategies: adhesively bonded carbon-fiber-reinforced polymer (CFRP) laminates and bolted steel plates (BSP). Four full-scale trapezoidal rib specimens containing fatigue-induced cracks were repaired and subjected to high-cycle loading representative of movable bridge conditions. Both repair methods suppressed observable crack growth within the test duration and shifted fatigue performance toward run-out behavior within the investigated stress range. Dynamic stiffness histories were monitored as a global indicator of load-transfer efficiency and overall structural response during cyclic loading. To interpret the experimental response mechanistically, a threedimensional fracture-mechanics framework was developed. Crack propagation was modeled using the virtual crack closure technique (VCCT) and a Paris-law formulation expressed in terms of strain energy release rate (Delta J). The fatigue crack system was represented by two interacting crack fronts with distinct local geometries, and a semi-inverse fracture-mechanics calibration framework was introduced to identify Paris-law parameters directly from experimentally measured crack-length histories. Automated finite element analyses generated Delta J response surfaces that enabled reconstruction of coupled crack-front evolution consistent with observed behavior. The calibrated parameters were validated through direct numerical integration and shell-based VCCT simulations. Close agreement between experiments and simulations supports the internal consistency of the proposed integrated experimental-numerical methodology within the tested cycle window and monitoring resolution. The results provide a full-scale assessment of lightweight repair effectiveness for fatigue-damaged RRBW connections and establish a validated framework for quantifying crack-driving force reduction, coupled crack-growth evolution, and stiffness recovery in orthotropic steel deck structures.
Keywords: Fatigue crack growth; Rib-to-rib butt-welded connections; Orthotropic steel decks; CFRP strengthening; Bolted steel plates; Failure analysis; Dynamic stiffness; Crack suppression; Finite element analysis; BEHAVIOR; JOINTS; Engineering; Materials Science